Tinjauan Antropologi Hukum terhadap Perilaku Masyarakat Kota Jambi Yang Tidak Menggunakan Kaca Spion pada Sepeda Motor di Jalan Raya - Dedy Syaputra (Universitas Batanghari Jambi, 2022)
Currently, there are still many motorcycle riders who do not use rear view mirrors on their motorbikes. With a legal event like this, the object of study in this study is the behavior of the people of Jambi City not using rear-view mirrors on motorbikes. The research method used in this research is empirical juridical so that this research is more descriptive in nature, the data sources are primary and secondary sources, the research approach is a case approach, the data collection technique in this study is a document study and the data analysis in this study was carried out qualitatively. . The results of the study indicate that the behavior of the people of Jambi City still commits violations of not using rear view mirrors on their motorbikes, the criminal sanctions that can be imposed are in Article 285 (1) of Law Number 22 of 2009 concerning Road Traffic and Transportation. and fines and ways to change the behavior of the people of Jambi City who do not use rear view mirrors on motorbikes on the highway are the application of criminal sanctions, socialization and installation of CCTV at crossroads by the Jambi City Police Traffic Unit and self-awareness from the people of Jambi City.